PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP NEGERI SEKECAMATAN TAMALATEA KABUPATEN JENEPONTO - Trisnawati H; Abdul Saman; Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to (1) provide an overview of the school principal's academic supervision in Public Junior High Schools in Tamalatea District; (2) provide an overview of teachers' work motivation in Public Junior High Schools in Tamalatea District; (3) provide an overview of teachers' performance in Public Junior High Schools in Tamalatea District; (4) analyze the influence of the school principal's academic supervision on the performance of teachers in Public Junior High Schools in Tamalatea District; (5) analyze the influence of work motivation on the performance of teachers in Public Junior High Schools in Tamalatea District; (6) analyze the combined influence of academic supervision and work motivation on the performance of teachers in Public Junior High Schools in Tamalatea District. This research employs a quantitative method with a correlational research design. The study was conducted at five schools in Tamalatea District, Jeneponto Regency, namely UPT SMP Negeri 1 Tamalatea, UPT SMP Negeri 2, UPT SMP Negeri 3, UPT SMP Negeri 4 Tamalatea, and UPT SMP Negeri 5. The results show that: The school principal's academic supervision in Public Junior High Schools in Tamalatea District is rated very good by teachers and has a positive impact on their performance. Teachers' work motivation is also high, with slight variation, indicating a supportive professional development environment. Teachers' performance is in the good category, although some teachers are in the moderate and low categories. Academic supervision and work motivation play a significant role in improving the quality of teachers' performance. Academic supervision contributes 29.2% to teachers' performance, while work motivation contributes 47.9%. Multiple regression analysis shows that academic supervision and work motivation together have a significant influence of 49.7% on teachers' performance.